Um capítulo singular no desenvolvimento da contabilidade financeira: o processo de harmonização contábil europeu - Gergull, Alberto Weimann (2022)
The consolidation of International Accounting Standards – IFRS, as a universal language, constitutes a milestone for science. How then to qualify the international cooperation project for editing and maintaining IFRS standards, the scientific-technological laboratory for the production of knowledge, technology and experimentation on a planetary scale, in real time and as companies and businesses continually reinvent themselves? The IFRS materialized in the utopia never imagined by the Securities and Exchange Commission (SEC), we suppose, when it stated that accounting information needed an international language in 1972. In 1973, the IASC was founded launching the first initiatives for the ambitious project that received contributions from multiple sources. But from the European Union would come the decisive move, putting all its weight in support of the IOSCO-IASC Agreement of 1995, with the perspective and effectively adopting the standards from 2005. A pioneer in the adoption of IFRS on a large scale, the European Union provided the necessary boost for the development, consolidation and dissemination of IFRS, and also emerged itself as the experimental laboratory and process model for the world